Smoking Cessation Interventions Amongst New Zealand Dental Students: A Survey. (5th August 2016) - Mistry, Deepa; Broadbent, Jonathan; Murray, Colleen
Abstract : Introduction: The NZ Government has set the goal of a smoke-free country by 2025. Research has shown that NZ dentists engage little in promotion of smoking cessation amongst their patients. The knowledge of, and attitudes towards, smoking cessation interventions of NZ dental students has not previously been reported. Aims: To investigate smoking cessation intervention practices of clinical dental students and explore perceived barriers to their delivery. Methods: A survey was conducted of all students in the three clinical years of the 5-year New Zealand dental training programme. Results: The response rate was 73.7%. At least half of the participants did not recall the inclusion of smoking cessation intervention information in the curriculum. The majority (70.9%) used a routine protocol to identify smokers. Almost two-thirds felt that smoking cessation interventions are important, whilst two-fifths felt it is their duty as a health professional. Lack of knowledge and time were the most common barriers. Conclusions: Although most dental students identify patients who smoke, the majority provide no cessation intervention services. This appears to be due to a lack of knowledge about available organisations and referral procedures. As future health professionals, dental students need better education in this area.